IMPLEMENTASI SUPERVISI PENDIDIKAN DI SD NEGERI KASONGAN BANTUL - Gunik Septiani (As-Sibyan, 2018)
This research is motivated by the fact that education staff must have enough equipment to be able to understand the goals of education, curriculum, operational instructional objectives, supervision, and help solve problems related to education. In this case, the principal must have sufficient equipment as above, so that the school being led has progress. Kasongan elementary school is one of the basic education institutions that has implemented a supervision program. In this study the focus af the study was planning, implementing, and evaluating educational supervision of the development of education in the kasongan public elementary school. This research is descriptive qualitative researc, data collection method through observation, interview and documentary methods. While the data analysis in this study uses the theory of Miles and Haberman whit the stages of data reduction, data display and conclusion drawing/ferification. The results of this study indicated that: educational supervision activities in Kasongan elementary school include planning, implementation, and avaluation. The planning activities, the principal plans a supervision program, schedule, and supervision. The implementation program, the principal controls learning in each class. The evaluation activities, in the final semester/final school year the principal gives the competency report cards owned according to the expertise of each teacher to improve competencies that are lacking and maintain good sompetencies.